Analysis of the adhesion of titanium and carbon-diamond coatings on 3D printed textured surfaces. (November 2019) - Zapata, A; V-Niño, E D; Endrino, J L; Fernández-Martínez, I; Díaz Lantada, A; Martinez, M; Pertuz, A
Abstract: The importance of coatings in engineering has been predominant throughout the development of the new industrial era. The competitiveness of the field has led to the development of better materials that achieve superior properties. The purpose of this research is evaluating the adhesion to the surfaces coated by magnetron sputtering technique. The adherence quality of the deposited coatings on specimens was evaluated adhesion by scratch and indentation tests guided according to standards, using the Tribolab UMT at constant load. The results obtained allow validating of the additive manufacturing process as possible mechanicals applications.